Nitrate reductase activity in sugarcane leaves in function of variations in the assay conditions. - Oliveira, Luiz Edson Mota de; Magalhães, Antonio Celso Novaes (Pesquisa Agropecuaria Brasileira, 2014)
The most appropriate conditions for in vitro nitrato reductase activity (NRA) assay in leaf tissue of two sugarcane varieties (NA 56 - 79 and CB 47 - 355) were studied. Above 50 mM NO-3, the NRA declined considerably. Such effect of high KNO3 levels on NRA was probably not related to the osmotic potential of the medium. In the absence of exogeneous NO-3, the NRA was negligible. Maximal NRA was obtained at pHs 7,5 and 8,5 for the varieties CB 47-355 and NA 56- 79, respectively. Maximal reduction of nitrate to nitrite was observed at 32° C for NA 56-79 and between 32°C and 37° C for CB 47 - 355. The maximal NRA occurred in the +3, +4 and +5 leaf (fully expanded leaves).